2017
DOI: 10.1158/0008-5472.can-16-1084
|View full text |Cite
|
Sign up to set email alerts
|

Role of Megakaryocytes in Breast Cancer Metastasis to Bone

Abstract: Little is known about how megakaryocytes may affect metastasis beyond serving as a source of platelets. In this study, we explored the functional implications of megakaryocyte accumulation in the femurs of mice after injection of metastatic or nonmetastatic breast cancer cells in 4T1.2 BALB/cJ and MDA-MB-231 nude mouse models. At bone metastatic sites, but not primary growth sites, tumor growth was associated with increased megakaryopoiesis in both model systems. In the orthotopic BALB/cJ model, extramedullary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…53 In addition, TPOdeficient mice, which are hemostatically compromised, exhibited more aggressive bone metastases in the syngeneic 4T1.2 breast cancer model. 54 Meanwhile, others have reported a reduced number of lung metastases of IV injected tumor cells in mice with experimental thrombocytopenia-associated hemostasis impairment. 38,55 Another study demonstrated that select chemotherapies are more effective in thrombocytopenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…53 In addition, TPOdeficient mice, which are hemostatically compromised, exhibited more aggressive bone metastases in the syngeneic 4T1.2 breast cancer model. 54 Meanwhile, others have reported a reduced number of lung metastases of IV injected tumor cells in mice with experimental thrombocytopenia-associated hemostasis impairment. 38,55 Another study demonstrated that select chemotherapies are more effective in thrombocytopenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…To support this, megakaryocytes have been reported to increase their number in response to cancer bone metastasis and inhibit prostate and breast cancer cell growth both in vitro and in vivo (48)(49)(50). Although the prognostic value and biological functions of megakaryocytes in cancer development and progression need to be further investigated, models that analyze the number difference between CTCs and megakaryocytes should be developed to make an efficient biomarker for survival prediction for patients with mCRPCs and potentially for other cancers as well.…”
Section: Discussionmentioning
confidence: 99%
“…190 However, this belief has been challenged by showing that an increase in megakaryocytes confers some measure of protection against metastasis. 199 In addition, neutrophils in circulation have been found to inhibit metastasis. 6,200 Blood sampling in 70 women with advanced-stage breast cancer showed a CTC-immune cell association.…”
Section: How Do Tumor Cells Survive In Circulation?mentioning
confidence: 99%